Corrugation Architecture Enabled Ultraflexible Wafer‐Scale High‐Efficiency Monocrystalline Silicon Solar Cell. Issue 12 (2nd January 2018) - Bahabry, Rabab R.; Kutbee, Arwa T.; Khan, Sherjeel M.; Sepulveda, Adrian C.; Wicaksono, Irmandy; Nour, Maha; Wehbe, Nimer; Almislem, Amani S.; Ghoneim, Mohamed T.; Torres Sevilla, Galo A.; Syed, Ahad; Shaikh, Sohail F.; et al.
Abstract: Advanced classes of modern application require new generation of versatile solar cells showcasing extreme mechanical resilience, large‐scale, low cost, and excellent power conversion efficiency. Conventional crystalline silicon‐based solar cells offer one of the most highly efficient power sources, but a key challenge remains to attain mechanical resilience while preserving electrical performance. A complementary metal oxide semiconductor‐based integration strategy where corrugation architecture enables ultraflexible and low‐cost solar cell modules from bulk monocrystalline large‐scale (127 × 127 cm 2 ) silicon solar wafers with a 17% power conversion efficiency. This periodic corrugated array benefits from an interchangeable solar cell segmentation scheme which preserves the active silicon thickness of 240 µm and achieves flexibility via interdigitated back contacts. These cells can reversibly withstand high mechanical stress and can be deformed to zigzag and bifacial modules. These corrugation silicon‐based solar cells offer ultraflexibility with high stability over 1000 bending cycles including convex and concave bending to broaden the application spectrum. Finally, the smallest bending radius of curvature lower than 140 µm of the back contacts is shown that carries the solar cells segments. Abstract : A corrugation architecture enabled ultraflexible, high performance crystalline ‐silicon solar cell on a 5 inch wafer via a lithography‐less, complementary metal oxide semiconductor compatible technique, shows power conversion efficiency of 17.2%, a bending radius lower than 140 µm with the groove width of 0.86 mm, and a high mechanical stability over 1000 cyclic bending.